Réponses

  • Utilisateur Brainly
2014-05-23T18:27:17+02:00
Résoudre chaque équation :

A) 3(x +7) = 4
3x + 21 = 4
3x = 4 - 21
3x = - 17
x = -17/3

B) 3(2 -3y) = - (y -2) 
6 - 9y = - y + 2
- 9y + y = 2 - 6
- 8y = - 4
y = - 4/-8
y = 0,5

C) -2 (a -1) = 4(2a +1)
- 2a + 2 = 8a + 4
- 2a - 8a = 4 - 2
- 10a = 2
a = 2/-10
a = -1/5
2014-05-23T18:30:25+02:00
3(x+7) = 4
ssi 3x + 21 = 4
ssi 3x = - 17
ssi x = - 17/3

3(2-3y) = - (y-2)
ssi 6 - 9y = -y + 2
ssi 6 - 2 = -y + 9y
ssi 4 = 8y
ssi y = 4/8
ssi y = 1/2 

-2(a-1) = 4(2a+1)
ssi -2a + 2 = 8a + 4
ssi 2 - 4 = 8a + 2a 
ssi -2 = 10a
ssi a = - 2/10
ssi a = -0.2